Curcumin Inhibits Polyethylene-Induced Osteolysis via Repressing NF-κB Signaling Pathway Activation - Senbo An; Fei Han; Yihe Hu; Yuwei Liu; Jingyi Li; Long Wang (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Aseptic loosening is a common reason for failed artificial hip replacement after total hip arthroplasty. Aseptic loosening is mostly the result of wear debris that causes osteolysis and weakens the structures that support the prosthesis. Wear debris plays a crucial role in osteolysis during the loosening process, and polyethylene (PE) particles are found as wear debris more frequently than any other type of particle. In the absence of effective therapeutic agents, osteolysis has been hard to treat. Previous studies have demonstrated that curcumin influences signalosome-associated kinases and the proteasome-ubiquitin system during osteoclastogenesis. The aims of this study were to explore the anti-osteolysis effect of curcumin and if possible to identify the signaling pathway involved in a model of PE-induced osteolysis. Methods: Differentiation of osteoclasts was induced in vitro by PE particles in RAW264.7 (monocyte/macrophage) cells and in vivo by calvarial and air pouch models of osteolysis established by PE stimulation in mice. We performed a set of TRAP staining, realtime polymerase chain reaction (PCR), and Western blot experiments to evaluate the anti-osteolytic effect of curcumin by comparing specimens that were exposed and not exposed to curcumin. Results: Curcumin had a promising inhibitory effect on osteolysis induced by wear debris and suppressed the RANK/c-Fos/NFATc1 signaling pathway. Conclusion: Curcumin can prevent PE-induced osteolysis and bone loss. An inhibitory effect on the RANK/c-Fos/NFATc1 signaling pathway may explain the anti-osteolysis activity of curcumin.